Electrocardiographic findings associated with cocaine use in humans: a systematic review. (January 2012) - Ramirez, F Daniel; Femenía, Francisco; Simpson, Christopher S; Redfearn, Damian P; Michael, Kevin A; Baranchuk, Adrian
Cocaine remains highly prevalent and accessible in the general population, continues to represent one of the most commonly reported substances in drug-related presentations to emergency departments, and is frequently implicated in drug-related deaths. Fatal cardiac arrhythmias are often suspected in the latter cases. In spite of this, its complex effects on the human cardiac conduction system remain poorly elucidated. In this article we sought to systematically review the medical literature to identify the electrocardiographic findings that have been linked to cocaine use in humans in an effort to highlight what physicians can expect to encounter when managing patients using the drug. The evidence is discussed, common findings are emphasized and clinical recommendations are proposed.